Global teamwork: The rise of collaboration in investigative journalism - Sambrook, R; Lewis, C; Alfter, B; Kayser-Bril, N; Koch, A; Clements, J (Reuters Institute for the Study of Journalism, 2018)
Recent major leaks of documents and data have seen new approaches to investigative journalism develop. Collaboration across countries and across organisations has been necessary to share the scale of the investigation, share expertise, and co-ordinate publication to maximise impact. This new model of collaboration, in an industry otherwise focused on exclusivity, indicates ways of adapting to technological, business and political change to strengthen accountability journalism at a time when it is under pressure from multiple directions. This book is a collection of essays from some of those closely involved in developing new models of collaboration in investigative journalism. It offers lessons from some of the recent major investigations, like The Panama and Paradise Papers and Edward Snowden’s NSA files, and a framework for others seeking to mount major collaborative investigations in future.